1982
DOI: 10.1073/pnas.79.23.7561
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative determination of dopamine receptor subtypes not linked to activation of adenylate cyclase in rat striatum.

Abstract: It is unlikely that either of the two classes of striatal sites are receptors for serotonin. The approach described will make it possible to assess the effects of physiological or pharmacological manipulations on the densities or properties of subtypes of dopamine receptors.The striatum is thought to contain multiple subtypes of dopamine receptors. Kebabian et aL (1) characterized a dopaminesensitive adenylate cyclase activity in the striatum. In vitro binding assays using the butyrophenones [3H]haloperidol an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…For example, the putative atypical neuroleptic, CGS 10746B, was shown to reduce 3-MT concentration in the ST (Alter et al, 1986). Similarly, the selective dopamine D1-receptor antagonist, SCH 23390 (Setler et al, 1978;Huff & Molinoff, 1982;Hytell, 1983), which shares many pharmacological features with CLZ (Lorio et al, 1983;Coward et al, 1989;Farde et al, 1989), has no effect on ST 3-MT accumulation (Boyar & Altar, 1987;Saller & Salama, 1986). The discordance between our findings and those of Saller & Salama, 1986, may result from methodological differences, e.g.…”
Section: Discussionmentioning
confidence: 50%
“…For example, the putative atypical neuroleptic, CGS 10746B, was shown to reduce 3-MT concentration in the ST (Alter et al, 1986). Similarly, the selective dopamine D1-receptor antagonist, SCH 23390 (Setler et al, 1978;Huff & Molinoff, 1982;Hytell, 1983), which shares many pharmacological features with CLZ (Lorio et al, 1983;Coward et al, 1989;Farde et al, 1989), has no effect on ST 3-MT accumulation (Boyar & Altar, 1987;Saller & Salama, 1986). The discordance between our findings and those of Saller & Salama, 1986, may result from methodological differences, e.g.…”
Section: Discussionmentioning
confidence: 50%
“…The affinities of DA antagonists for E3H]Spi sites are slightly increased by GTP in the CHAPSO-solubilized preparations. This finding suggests that the subclass of D-2 DA receptors, which is negatively coupled to adenylate cyclase (Frey et al, 1982;Huff and Molinoff, 1982), was extracted by CHAPSO from the striatal membranes, or that GTP reciprocally modulates the conversion by agonists and antagonists of the low-and high-affinity forms of the receptor. It is noteworthy that the reciprocal modulation by agonist and antagonist of two different forms of the receptor under the influence of guanine nucleotides was suggested for the membrane-bound DA receptor in the porcine anterior pituitary (De Lean et al, 1982).…”
Section: Treatmentmentioning
confidence: 99%
“…In addition to the D-1 and D-2 DA receptor binding sites, the existence in the brain of other putative DA receptor binding sites, namely D-3 and D-4 sites, was reported (Titeler et al, 1979;Sokoloff et al, 1980). Radioligand binding studies have also revealed the existence of two subtypes of D-2 DA receptors, one of which is affected by guanine nucleotides (Huff and Molinoff, 1982). However, it is not established whether these multiple binding sites represent distinct molecular entities or different states of the same DA receptor.…”
mentioning
confidence: 99%
“…However that study did not differentiate between binding to D, and 5-HT2 sites. Using tissue from frontal cortex, the K D of spiperone for 5-HT2 sites has been estimated to be 1.0 x M (Huff and Molinoff, 1982). Thus if striatal and frontal cortical 5-HT2 sites have equal affinities for spiperone, then 6 x M [3H]spiperone should have labelled a significant portion of the striata15-HT2 sites and this may have accounted for the multiphasic nature of the binding.…”
Section: Discussionmentioning
confidence: 99%